Dinaphthotetrathienoacenes: Synthesis, Characterization, and Applications in Organic Field‐Effect Transistors. Issue 19 (16th March 2022) - Jouclas, Rémy; Liu, Jie; Volpi, Martina; Silva de Moraes, Lygia; Garbay, Guillaume; McIntosh, Nemo; Bardini, Marco; Lemaur, Vincent; Vercouter, Alexandre; Gatsios, Christos; Modesti, Federico; Turetta, Nicholas; et al.
Abstract: The charge transport of crystalline organic semiconductors is limited by dynamic disorder that tends to localize charges. It is the main hurdle to overcome in order to significantly increase charge carrier mobility. An innovative design that combines a chemical structure based on sulfur‐rich thienoacene with a solid‐state herringbone (HB) packing is proposed and the synthesis, physicochemical characterization, and charge transport properties of two new thienoacenes bearing a central tetrathienyl core fused with two external naphthyl rings: naphtho[2, 3‐b]thieno‐[2′′′, 3′′′:4′′, 5′′]thieno[2″, 3″:4′, 5′]thieno[3′, 2′‐b]naphtho[2, 3‐b]thiophene (DN4T) and naphtho[1, 2‐b]thieno‐[2′′′, 3′′′:4′′, 5′′]thieno[2′′, 3′′:4′, 5′]thieno[3′, 2′‐b]naphtho[1, 2‐b]thiophene are presented. Both compounds crystallize with a HB pattern structure and present transfer integrals ranging from 33 to 99 meV (for the former) within the HB plane of charge transport. Molecular dynamics simulations point toward an efficient resilience of the transfer integrals to the intermolecular sliding motion commonly responsible for strong variations of the electronic coupling in the crystal. Best device performances are reached with DN4T with hole mobility up to μ = 2.1 cm 2 V −1 s −1 in polycrystalline organic field effect transistors, showing the effectiveness of the electronic coupling enabled by the new aromatic core. These promising results pave the way to the design of high‐performing materials based on this new thienoacene, notably through the introduction of alkyl side‐chains. Abstract : The synthesis, physicochemical characterization, and charge transport of two new herringbone packing thienoacenes bearing a central tetrathienyl core fused with two external naphthyl rings are presented. Naphtho[2, 3‐b]thieno‐[2′′′, 3′′′:4′′, 5′′]thieno[2″, 3″:4′, 5′]thieno[3′, 2′‐b]naphtho[2, 3‐b]thiophene (DN4T) qualifies as one of the best conjugated core for organic field effect transistor applications, thanks to its resilience to dynamic disorder, affording a hole mobility of 2.1 cm 2 V −1 s −1 in polycrystalline films.